Partial gastrectomy for stomach necrosis in a 13-year-old child four years after Nissen fundoplication - Alice Pitout; Charles Mazeaud; Julie Lienard; Olivier Larmure; Jean-Louis Lemelle; Nicolas Berte (Elsevier, 2022)
NISSEN fundoplication is a common procedure for the management of gastroesophageal reflux disease. It can have the side effect of a ''gas bloat syndrome'', an accumulation of air responsible for functional symptoms and gastric distension. Gastric necrosis due to gastric distension is a rare event, but with a high mortality rate in case of delayed diagnosis.We describe the surgical management of a partial necrosis of the stomach in a 13-year-old boy with mental retardation. Exploratory laparotomy revealed extensive gastric necrosis without perforation. We performed a partial gastrectomy, without removal of the NISSEN, with reinstatement of gastrostomy, drainage and antibiotic therapy. A posterosuperior gastric fistula appeared in following, leading us to perform a feeding jejunostomy.After three months, the patient was able to return home, fed on the jejunostomy.This is the first pediatric case of partial necrosis of the stomach in the aftermath of a NISSEN, managed by partial gastrectomy. In case of suspected gastric necrosis, an emergency laparotomy associated with a digestive resection procedure seems to be the most indicated. Our case proves that even in case of extensive necrosis, a partial gastrectomy more or less associated with a controlled fistulation can be attempted.